Novel feline viruses: Emerging significance of gammaherpesvirus and morbillivirus infections. Issue 1 (January 2019) - Beatty, Julia A; Sharp, Claire R; Duprex, W Paul; Munday, John S
Practical relevance: New technologies capable of sequencing the genetic material in any given biological sample, combined with computer-based algorithms for sequence assembly and analysis, have revolutionised infectious disease research. The rate at which novel viruses are being discovered now exceeds our understanding of their clinical relevance. Novel viruses may contribute to diseases that are major causes of feline morbidity and mortality, including cancer and chronic kidney disease. The identification of new viral pathogens raises the prospect of not only improved patient outcomes through specific treatment but even disease prevention through viral control measures. Clinical challenges: It can be difficult to determine the role of a novel virus in disease development. Disease may be an occasional outcome, often years after infection. A high prevalence of infection in the general population can make disease associations harder to identify and almost impossible to rule out. Host cofactors such as immune dysfunction, genetic background or coinfections may be required for manifestation of disease, and one virus species may be linked to a range of pathological sequelae. Establishing causality relies on evaluating accumulating evidence from multiple investigations, which is often hard to access by practitioners. Global importance: The worldwide distribution of gammaherpesvirus and morbillivirus infections in domestic cats underlines the potential of these viruses to negatively impact feline health and welfare globally. Evidence base: This review relies on grade Ia–III evidence.